(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The barangay is the smallest administrative unit that contributes to a community’s economic growth. Its main purpose is to enhance the welfare of the people by increasing their income, providing more jobs, and improving the social and natural environment. Barangay ABC residents have been enjoying the benefits of various projects and developments undertaken by their local government. They also devise different plans to ensure their district’s future progress. Regarding document processing, Barangay ABC follows specific steps by the Secretarial Department. This study aims to identify long-term concerns affecting their procedures, provide solutions, and determine possible alternatives. Researchers used a qualitative method by conducting open-ended surveys and interviews with the Secretarial Department of Barangay ABC. The data gathered was analyzed and approved by the respondents. Based on the recommendations, the respondents agreed to implement an online application form to enhance document processing, establish a database to keep records and track information, enforce a verification process for SAP benefits, and set a schedule for document release upon request. These enhancements are expected to improve productivity, reduce paper consumption, and provide a smooth operation.